Endoscopic snare papillectomy: a possible radical treatment for a subgroup of T1 ampullary adenocarcinomas - Petrone, G.; Ricci, R.; Familiari, P.; Inzani, F.; Matsuoka, M.; Mutignani, M.; Delle Fave, G.; Costamagna, G.; Rindi, G. (Endoscopy, 2013)
Pancreaticoduodenectomy is the standard care for invasive ampullary adenocarcinomas. However, endoscopic snare papillectomy (ESP) might play a curative role in very selected patients. We studied a series of 15 patients with T1 ampullary adenocarcinoma who were treated by ESP alone and followed up for a mean of 29.6 ± 21.9 months (range 8 – 81 months). ESP was curative for eight patients (57.1 %). No tumor-related death was observed in patients with a cancer infiltration depth of ≤ 4 mm. According to this preliminary experience, we suggest that this measurable variable threshold should be considered as a possible basis for future large-scale studies.